2018
DOI: 10.1109/toh.2018.2825396
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Methodology to Characterize the Intrinsic Material Properties of Compliant Test Stimuli

Abstract: Understanding how we perceive differences in material compliance, or 'softness,' is a central topic in the field of haptics. The intrinsic elasticity of an object is the primary factor thought to influence our perceptual estimates. Therefore, most studies test and report the elasticity of their stimuli, typically as stiffness or modulus. However, many reported estimates are of very high magnitude for silicone-elastomers, which may be due to artifacts in characterization technique. This makes it very difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Hence, care should be given to their mechanical characterization. Nevertheless, so far, mechanical characterization of these specimens for the psychophysical investigation of haptic perception has been nonstandard, and the recent work by Gerling et al is an important step towards solving this problem [74]. More specifically, tuning the viscoelastic properties of a silicone rubber while controlling its material nonlinearities is a challenge that has not been solved yet.…”
Section: Effect Of (Presence Of) Visual and (Lack Of) Tactile Feedbackmentioning
confidence: 99%
“…Hence, care should be given to their mechanical characterization. Nevertheless, so far, mechanical characterization of these specimens for the psychophysical investigation of haptic perception has been nonstandard, and the recent work by Gerling et al is an important step towards solving this problem [74]. More specifically, tuning the viscoelastic properties of a silicone rubber while controlling its material nonlinearities is a challenge that has not been solved yet.…”
Section: Effect Of (Presence Of) Visual and (Lack Of) Tactile Feedbackmentioning
confidence: 99%
“…However, a clear picture has yet to emerge from this work because both tactile cues believed to be important in the perception of softness (i.e., indentation depth and contact area) are affected simultaneously by the mechanical properties (e.g., Young’s modulus, stiffness). In a critical review, Gerling et al ( 20 ) found several instances in which the relationships between the mechanical properties of test objects and the participant’s responses to them were unclear. In some studies, it was difficult to connect participant responses with mechanical properties because of the unreliable control over the mechanical properties of samples ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a critical review, Gerling et al ( 20 ) found several instances in which the relationships between the mechanical properties of test objects and the participant’s responses to them were unclear. In some studies, it was difficult to connect participant responses with mechanical properties because of the unreliable control over the mechanical properties of samples ( 20 ). In other instances, some studies were regarded as ambiguous because it was assumed that controlling the intrinsic mechanical properties would automatically control the extrinsic properties such as the indentation depth and contact area on the finger ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…We produced softness stimuli with different elasticity by mixing a two-component silicon rubber solution (AlpaSil EH 10:1) with different amounts of silicon oil (polydimethylsiloxane, viscosity 50 mPa/s) and pouring it into cylindrical plastic dishes (75 mm diameter × 38 mm height). We produced in total 10 To characterize the elasticity of the stimuli we adopted the standard methodology proposed by [22]. From the solution mixed for every stimulus a portion was poured into a small cylinder (10 mm thick, 10 mm diameter) to obtain standardized substrates of the same material for the measurement.…”
Section: Softness Stimulimentioning
confidence: 99%